Examining the Urgency of Adab-Based Learning : A Hadith Perspective on the Global Ethical Crisis - Ahmad Fauzan; Muhammad Asrori (Pustaka Peradaban, 2025)
The global ethical crisis, marked by increasing unethical behavior such as corruption and social conflict, necessitates an educational approach that instills moral and ethical values. This article examines the urgency of adab-based learning as a potential solution, drawing upon hadith of the Prophet Muhammad SAW and relevant literature. Using a literature study approach, this research reveals the hadith's explicit emphasis on character building through adab, including respect for teachers, politeness, and integrity. Consequently, implementing adab values in education is crucial for developing individuals with noble morals who can contribute to mitigating the global ethical crisis. This study suggests that adab-based education offers a valuable framework for addressing contemporary ethical challenges.